(untitled) (International Journal of Advanced Research in Computer Science, 2017)
Time is an expensive resource and it is an asset to those who respect and use it efficiently. As regards information delivery services, there have been so much delay and loss of information packets in the process of delivery. In this study, we demonstrate the effect of a scheduling algorithm on the speed and reliability of information delivery.Anew decentralized scheduling algorithm and mail delivery and an example of manual mail delivery samples is presented to prove the effect of a proposed scheduling tool on information packets distribution. We useda set of mail information from a private mail bag as locations against some resource agents used in delivering the mail and we applied the algorithm on these locations to see its effects on the time of delivery. The time spam was studied from applying the algorithm and from manually sorting them. The comparism showed differences in the time duration. The research demonstrates the influence of scheduling algorithm on the delivery of mails.We concluded that handling mail procedures using a decentralized scheduling algorithm would have great effects on information management and transfer. These effects should be considered in setting up any information services especially, one with many users. Key words:information delivery, mail, scheduling packets, algorithm data sorting.